TRANSFORMATION OF MANAGEMENT STYLES IN THE CONTEXT OF REMOTE WORK - Ma. Yuzhen (Innovate Conferences, 2025)
The COVID-19 pandemic and rapid digitization have accelerated the transition to remote work, leading to a fundamental shift in management approaches. This thesis explores how traditional management styles have evolved in response to remote work environments, focusing on the increasing relevance of transformational, participative, and digital leadership. By analyzing current practices in various industries, the study highlights the challenges and benefits of managing remote teams and offers strategic recommendations for sustainable management in virtual settings.
Keywords: Remote work, management styles, transformational leadership, digital leadership, organizational behavior, remote teams, communication, productivity, motivation, leadership transformation